2019
DOI: 10.1136/bmjopen-2018-028093
|View full text |Cite
|
Sign up to set email alerts
|

Are perioperative interventions effective in preventing chronic pain after primary total knee replacement? A systematic review

Abstract: ObjectivesFor many people with advanced osteoarthritis, total knee replacement (TKR) is an effective treatment for relieving pain and improving function. Features of perioperative care may be associated with the adverse event of chronic pain 6 months or longer after surgery; effects may be direct, for example, through nerve damage or surgical complications, or indirect through adverse events. This systematic review aims to evaluate whether non-surgical perioperative interventions prevent long-term pain after T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 102 publications
1
31
0
1
Order By: Relevance
“…The protocol for this systematic review was registered with PROSPERO 49. We formulated the research question according to the participants, intervention(s), comparator(s), outcomes (PICO) principle50 and used methods based on those recommended by Cochrane 51.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The protocol for this systematic review was registered with PROSPERO 49. We formulated the research question according to the participants, intervention(s), comparator(s), outcomes (PICO) principle50 and used methods based on those recommended by Cochrane 51.…”
Section: Methodsmentioning
confidence: 99%
“…We established a database of all randomised controlled trials in knee replacement, in preparation for a suite of systematic reviews in chronic pain after TKR 47 48. Relevant trials were identified through searches (last updated on 18 December 2018) in: MEDLINE, Embase and PsycINFO on OvidSP; CINAHL on EBSCOhost; and The Cochrane Library .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Several studies have investigated factors that may affect the risk of persistent postsurgical pain. [7][8][9][12][13][14][15][16][17][18][19] However, data on the effects of spinal and general anesthesia on persistent pain after total knee arthroplasty are highly limited. A retrospective, multicenter study including patients who underwent hip or knee arthroplasty found no difference in the prevalence of persistent postsurgical pain between the regional and general anesthesia groups.…”
mentioning
confidence: 99%